Chitosan as a removing agent of beta-lactoglobulin from membrane models - Caseli, Luciano (Langmuir : the ACS journal of surfaces and colloids, 2008)
Many chitosan biological activities depend on the interaction with biomembranes, but so far it has not been possible to obtain molecular-level evidence of chitosan action. In this article, we employ Langmuir phospholipid monolayers as cell membrane models and show that chitosan is able to remove beta-lactoglobulin (BLG) from negatively charged dimyristoyl phosphatidic acid (DMPA) and dipalmitoyl phosphatidyl glycerol (DPPG). This was shown with surface pressure isotherms and elasticity and PM-IRRAS measurements in the Langmuir monolayers, in addition to quartz crystal microbalance and fluorescence spectroscopy measurements for Langmuir-Blodgett (LB) films transferred onto solid substrates. Some specificity was noted in the removal action because chitosan was unable to remove BLG incorporated into neutral dipalmitoyl phosphatidyl choline (DPPC) and cholesterol monolayers and had no effect on horseradish peroxidase and urease interacting with DMPA. An obvious biological implication of these findings is to offer reasons that chitosan can remove BLG from lipophilic environments, as reported in the recent literature